Vergilius Provence-ban: Marcel Pagnol Bucolica-fordítása II. - Pataki, Elvira (Antikvitás & Reneszánsz, 2019)
In the long history of French translations of Vergilian Eclogues, the work of M. Pagnol (1895–1974) has a special place. The novelist, playwright and filmmaker (the first one of them elected to Académie Française) published his version of pastoral poems in 1958, two years after the highly artistic edition of P. Valéry. In a sociocultural approach, Pagnol’s translation is usually considered as a sophisticated tool of marketing used to remodel the image of the author. The popular and rich star of French theatre and cinema is not really accepted neither by academic literature nor by the movements of literary radicalism because of his regional features and his cheap sentimentalism. By translating Virgil in a quasi-academic way, by editing a text with a preface, commentary and notes, Pagnol would highlight his erudition and postulate a place for himself among the Classics. Nevertheless, his very funny and personal way to interpret Virgil, his cultural commentaries, and his ethical remarks based on the norms of modern urban society make the Latin poet accessible for a very wide audience. The current paper focuses on the aesthetic features of his work. Being born in Provence, passionate of the Mediterranean landscape and highly influenced by classical mythology, Pagnol appears to emphasize the Latin origins of his homeland, the cultural and ethnical continuity between the Antiquity and the 20th century, with a strong apparent wish to revive thousand-year-old traditions.